Dvoruk V.I., Borak K.V. Research of wear-resistance working organs of disk tillage machinery - Дворук, В.А.; Борак, К.В. (Problems of Tribology, 2017)
The structural features of the material of Bellota'і disk tillage organs are considered. The tribotechnical characteristics of this material are analyzed and it shows that in comparison with the material which is mainly used by domestic manufacturers of disk working bodies (steel 65G), it possesses ,.5 times more wear-resistance. It was established that increasing the wear resistance and achieving the self-closing effect in Bellota's disk work-ing organs was obtained through the use of high-quality steel and complex heat treatment, which allowed to achieve the qualitative tribo-technical characteristics of the wearing surface. Despite the high wear resistance of the disk working organs of tillage -working machines, even such a world leader as Bellota does not take into ac-count the tillage -climatic conditions of operation in the design and production of working organs, therefore it is promising to determine the necessary tribotechnical characteristics of the friction surfaces of the working organs of tillage-working machines for each tillage -climatic zone, that will allow to make working organs with the in-creased wear-resistance, taking into account the conditions of their operation.